Dakwah Virtual Ustadz Ramdan Juniarsyah pada Akun Youtube Dakwah Wayang Official - Fitria, Nurul; Lutfi Latifah, Siti; Ariyanto, Budi; Zainab, Dwi (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This research aims to analyze the virtual preaching delivered by Ustadz Ramdan Juniarsyah through the YouTube account Dakwah Wayang Official. The research method employed is content analysis with a qualitative approach. Data were collected through observations of preaching videos uploaded on the YouTube channel. The findings indicate that Ustadz Ramdan Juniarsyah's virtual preaching via the Dakwah Wayang Official YouTube account has its own distinctive characteristics in delivering the message of preaching. This research provides a deeper understanding of the use of social media as a means of preaching, as well as Ustadz Ramdan Juniarsyah's contribution to disseminating religious messages through digital platforms.